Trends of rhinoplasty research in the last decade with bibliometric analysis - Zhu, Xuanru; Zhang, Bin; Huang, Yuesheng (Frontiers in Surgery, 2023)
Background: As rhinoplasty(RP) with different requirements is becoming more and more popular in the latest decade, this study aims to quantitatively and qualitatively explore the trends in RP research, depict research hotspots, and point out the future direction with bibliometric analysis. Methods: All RP literatures in last decade (from 2012 to 2021) were retrieved from Web of Science Core database. Annual output, institutions, authors, journals and most-cited literatures were analyzed by bibliometric tools, including citespace, bibliometric online platform, bibliometrix R language kit, BICOMB and gCLUTO. Results: A total of 2,590 RP research literatures dated between 2012 and 2021 were included according to our criterion. As for the country, the USA, Turkey and Korea maintained the top 3 in RP research. As for the institutions, the University of California, Irvine, Stanford University and University of Ulsan ranked top 3 in RP research publications basing on article counts. Professor Rhorich RJ, Most SP and Jang YJ were the most contributed authors according to article counts and citation number. The top journals were The plastic and reconstructive surgery, JAMA Facial Plastic Surgery and Aesthetic Surgery Journal. The 10 most-cited literatures were also listed explicitly in this study. Lastly, biclustering analysis on most frequent keywords were conducted which helped to identify seven hotspots clusters in RP research. Conclusions: We comprehensively summarized the publication information of RP literatures in past decade, highlighted the current status and trends over time and provide guidance for in-depth research direction on RP for the future.